2004
DOI: 10.2139/ssrn.923544
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, Trade Policy and Trade Flows

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 31 publications
5
31
0
3
Order By: Relevance
“…Anderson and Marcouiller (2002) showed that better institutional quality leads to larger trade volumes. A similar positive influence of domestic institutions on bilateral trade flows was found by Jansen and Nordås (2004). Absence of good governance, especially a weak regulatory framework, can be an obstacle to trade (Méon & Sekkat, 2008).…”
Section: Institutional Quality As a Determinant Of Exportssupporting
confidence: 57%
“…Anderson and Marcouiller (2002) showed that better institutional quality leads to larger trade volumes. A similar positive influence of domestic institutions on bilateral trade flows was found by Jansen and Nordås (2004). Absence of good governance, especially a weak regulatory framework, can be an obstacle to trade (Méon & Sekkat, 2008).…”
Section: Institutional Quality As a Determinant Of Exportssupporting
confidence: 57%
“…151 Njinkeu et al (2008) 0.167 Wilson et al (2004) 0.202 Martinez-Zarzoso, Nowak-Lehmann (2003) 0.211 Fujimura, Edmonds (2006) 0.389 Ninkovic (2009) 0.442 De (2007) 0.445 UN Economic Commission for Africa (UNECA) (2013) 0.518 Vijil, Wagner (2012) 0.925 Portugal-Perez, Wilson (2012) 1.014 Marquez-Ramos, Martinez-Zarzoso (2005) 1.047 Iwanow, Kirkpatrick (2007) 1. 969 Bouet et al (2008) 2.013 Elbadawi et al (2006) 7.348 Granato (2008) 7.727 Raballand (2003) 0.000 Grigoriou (2007) 0.006 Bandyopadhyay (1999) 0.012 Carrere (2006) 0.012 Jansen, Nordås (2004) 0.014 Brun et al (2005) 0.016 Martinez-Zarzoso, Nowak-Lehmann (2003) 0.02 Wilson et al (2004) 0.026 Nordas, Piermartini (2004) 0.067 Kurmanalieva, Parpiev (2008) 0.116 Persson (2007) 0.118 De (2007) 0. 147 Njinkeu et al (2008) 0.149 Iwanow, Kirkpatrick (2009) 0.461 Fujimura, Edmonds (2006) 0.541 Marquez-Ramos, Martinez-Zarzoso (2005) 0.541 Lawless (2010) 0.672…”
Section: Model Predictionmentioning
confidence: 99%
“…Moreover, the study also found that the supply response to a reduction in tariffs is larger the higher the penetration rate of telecommunications (Box IIB.6 and Jansen and Nordås, 2004). However, anecdotal evidence suggests that new technology can sometimes also create barriers between those connected and those not connected in low-income countries.…”
Section: B Infrastructure In Trade and Economic Developmentmentioning
confidence: 88%